Approaching Inclusion as Social Practice: Processes of Inclusion and Exclusion - Hansen, Janne Hedegaard; Jensen, Charlotte Riis; Lassen, Mikkel Christian; Molbæk, Mette; Schmidt, Maria Christina Secher (Journal of Educational and Social Research, 2018)
The article presents the results of a review of international research investigating mechanisms and processes of inclusion and exclusion as an ongoing part of social practice in a school context. The review forms part of a research project investigating the social practices of inclusive education in primary and lower-secondary education (age 6–16) in public schools as constituted by processes of inclusion and exclusion. The project aims to shift the scientific focus of research in inclusive education from the development of pedagogical and didactic practice to the importance of community construction through inclusion and exclusion processes. The project arises in context of Danish education policy, while the review looked for international research findings on the limits between inclusion and exclusion: how they are drawn, by whom, for what reasons, and for whose benefit? On the background of the review, we conclude that there seems to be a pattern of inclusive school practice leading to a specific social order that limits inclusion. The review also shows that the construction of the ideal student through various kinds of markers has a huge impact on these limits. A twin-track approach that combines research in the development of inclusive learning environments with research in the constitution of social practice in a school context will produce knowledge of the relation between inclusive school practice and the reproduction of social structures and patterns of inequality.